1997
DOI: 10.1002/ange.19971091228
|View full text |Cite
|
Sign up to set email alerts
|

Elektrochemisch induzierte Lumineszenz und protonengesteuerte Fluoreszenzlöschung mit funktionalisierten Difluorboradiaza‐s‐indacenen

Abstract: Zwei der acht unabhangigen Perfluoralkylketten in der asymmetrischen Einheit von 4 weisen planare, gestaffelte Konformationen rnit Torsionswinkeln von 177.2 und 178.3" in der Kette auf. Dies liegt wahrscheinlich an lokalen Packungskrlften, was d a m fuhrt, daD dies, Ketten ahnlich wie die in 1 dicht gepackt sind. SchlieDt man diese Werte aus, liegen die Torsionswinkel in 4 zwischen 154.7" und 173.7".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
2
12
0
6
Order By: Relevance
“…Figure 1 shows that the indacene plane of 1 a is almost planar with the average deviation of the ring atoms amounting to 0.0135 , which is similar to the classic BODIPY derivatives. [19,29,[52][53][54][55][56][57][58][59][60] The bond lengths and angles of the indacene ring system are also close to the values of previously reported BODIPY compounds. The molecules are packed parallel to each other with alternating tail-to-tail orientation along the crystallographic a axis (Figure 2).…”
Section: Resultssupporting
confidence: 67%
“…Figure 1 shows that the indacene plane of 1 a is almost planar with the average deviation of the ring atoms amounting to 0.0135 , which is similar to the classic BODIPY derivatives. [19,29,[52][53][54][55][56][57][58][59][60] The bond lengths and angles of the indacene ring system are also close to the values of previously reported BODIPY compounds. The molecules are packed parallel to each other with alternating tail-to-tail orientation along the crystallographic a axis (Figure 2).…”
Section: Resultssupporting
confidence: 67%
“…The ICT state should be formed by the transfer of one electron from the electronic p system of the PM chromophore to the cyano group, and it could induce a new nonradiative deactivation from the local excited state, as is illustrated in Scheme 1. A similar but inverse electron transfer for an electron-donor substituent (aniline) to the electronic p system of a PM chromophore was previously reported by Rurack et al [32][33][34][35] for the observed declination of the fluorescence intensity of the corresponding PM derivative. The ICT state of PM650 should not be fluorescent under the experi- mental conditions used in this work, since an additional emission band at lower energies with respect to the S 1 fluorescence band was not experimentally observed in polar/protic solvents.…”
Section: Solvent Effects: Radiative and Nonradiative Deactivation Ratsupporting
confidence: 73%
“…However, the presence of high electron-donor or acceptor groups in the molecular structure can modify the photophysical properties of these dyes in such a way that it can enlarge the tunability range and/or improve their photostability and/or laser efficiency. In this regard, Jones et al [31] recently reported drastic changes in the photophysical properties of PM dyes in the presence of a cyano group, and Rurack et al [32][33][34][35] also reported an intramolecular charge-transfer state between an aniline group at the 8 position and the electronic p system of the PM chromophore. In this system, the electronic excitation leads to an electron transfer from the aniline group to the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, improved sensitivity can be obtained when the sensing event perturbs a charge‐transfer excited state or interrupts intramolecular electron transfer 66. Daub and Rurack67 were the first to show the high potential for Bodipy dyes in this field, and their original research has been followed by countless examples of Bodipy‐based fluorescent molecular sensors. A brief summary of the field is given in Sections 4.1–4.5.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…The nitrogen donor can be protonated at low pH value or upon addition of acid to an organic solvent, so that light‐induced electron transfer is curtailed. This protonation results in the restoration of normal Bodipy fluorescence 67. By changing the nature of the donor, or by systematic alteration of its reduction potential, the pH range over which fluorescence modulation occurs can be tuned.…”
Section: Chemical Sensorsmentioning
confidence: 99%